Kontribusi KH. Mustofa Bisri Terhadap Pengembangan Pemikiran Hukum Islam di Indonesia - Dri Santoso (STAIFAS-Press, 2021)
This article is about muslim religious of teacher thoughts. Mustofa Bisri on the development of Islamic law and his new thoughts on legal issues that he answered. Other important contributions given by muslim religious of teacher Mustofa Bisri is his attitude in issuing fatwas that is not bound by a particular madhhab. This attitude becomes important in the midst of encouraging the development of Islamic legal thought which requires freedom of thought and is not tied to a particular madhhab. Of course the freedom of thought is muslim religious of teacher version. Mustofa Bisri is a freedom that is measured and framed in the maqasid al-shar'iyyah which is the purpose of the revelation of Islamic shari'ah the implication is a fact that there is a gap between the nass-nass of law that is very limited and the issues of life that are not limited. To provide a solution to the gap that exists today, the Qur'an and al-H adith as a source of complete Islamic teachings in the sense of the basic principles of law with its various aspects must be understood with the methods of ijtihad with emphasis on the maqasid ash -shari'ah.